The Effect of Bruxism on the Severity of OSAS in Patients with OSAS and Headache - Yeşim Güzey Aras; Sena Boncuk; Figen Yavlal (Sakarya Tıp Dergisi, 2023)
OBJECTIVE: Morning headaches have been associated with sleep-related breathing disorders and Sleep Bruxism (SB). The present study aims to investigate the relationship between SB, primary headaches and the severity of Obstructive Sleep Apnea Syndrome (OSAS) in patients presenting with morning headaches and a prediagnosis of OSAS. MATERIALS AND METHODS: The study included 480 patients who prediagnosis of OSAS and morning headache complaints, and were diagnosed with primary headache according to the International Classification of Headache Disorders (ICHD). Age, gender, Body Mass Index (BMI), headache type, presence of SB, OSAS stage according to Apnea-Hypopnea Index (AHI), and presence of hypoxia were recorded. Patients were then divided into 2 groups of SB (-) and SB (+), and both groups were compared in terms of headache. RESULTS. In the classification according to headache types, 31.5% of the patients were classified as migraine, 41.9% as tension-type headache (TTH), 2.1% as cluster, and 24.6% as other types of headache. While 76% of the patients had no SB, 24% had SB. The rate TTH was significantly (p